Associação de raça com variáveis de funcionalidade, composição corporal e atividade física em idosos atendidos pela estratégia da saúde da família do município de Porto Alegre - Schopf, Pâmela Pissolato (2016)
Introduction: The aging process is marked by changes in the human body, causing progressive loss in different functions. Muscles account for approximately 40% of total body mass and are one of the tissues that suffer the most from the impact of aging, showing progressive and linear decline in quantity as well as function. A positive association between musculoskeletal tissue and age is observed until the threshold of 27 years old, which does not differ significantly between ethnic groups and gender, but after this period there is a negative association between these variables. Objective: To investigate the association of race with variables related to function, body composition and physical activity in older adults registered in the Family Health Strategy in the city of Porto Alegre. Methods: Cross-sectional, observational, retrospective study. The studied population consisted of older men and women over the age of 60 years old, registered and accompanied by the Family Health Strategy (FHS) in the city of Porto Alegre and evaluated by the EMISUS Project. The sample consisted of 390 older adults, 272 were white and 118 were black. The collected variables were: sociodemographic and anthropometric data, functional capacity, muscle strength, mobility and physical activity level. The instruments used for data collection were: tape measure, adipometer, chair stand test, strength dynamometer, 4.6m-walk test and Minnesota Leisure-time Physical Activity (LTPA) Questionnaire. The sample was adjusted for sex, age, marital status and education. Results: Participants mean age was 68.0 ± 6.3 years and 68.9 ± 6.5 years for white and black older adults respectively (p= 0.203).Marital status and education showed statistically significant differences between the two groups (p= 0.015 and p= 0.013), the majority the elderly whites self-reported, 106 (39.4%) were single and 42 (35.9%) separated between self-reported black elderly. In relation to education the majority the white and black elderly self-reported had reported between 1-3 years of study, 76 (28.0%) white elderly and 35 (29.9%) of black elderly, respectively. Black older adults had significant greater muscle mass (MM) than older whites, (34.74 ± 5.62 and 33.15 ± 5.78; p= 0.014 respectively), but on the other hand, had lower means of lower limbs strength comparing to older whites (8.36 ± 2.86 and 9.05 ± 3.34; p= 0.053). No statistically significant differences between blacks and whites were found in calf circumference (cm) (31.99 ± 4.01 and 31.84 ± 3.42; p= 0.101), muscle mass index (14.06 ± 2.55 and 13, 59 ± 2.52; p= 0.095), gait speed (m/s) (6.83 ± 1.83 and 6.46 ± 1.94; p= 0.080), caloric (kcal) (3606,34 (1896,61-5877,59) e 3163,42 (1532,37-7283,50); p= 0,785) and time expenditure in physical activities (min) (180,00 (79,25-531,25) e 180,00 (77,00-542,25); p= 0,793). Conclusion: Older adults with black self-reported had higher muscle mass than those of white ethnicity, but less strength in lower limbs. These findings corroborate the literature with regard to the higher amount of muscle mass presented by black individuals throughout life; however, it brings the need for further studies in order to investigate the quality of the tissue as muscle fibers, especially in lower limbs, decrease progressively, which make these older adults more prone to falls and disabilities.